Análisis y mejora de los procesos y procedimientos administrativos y operativos del GADPR de Canuto del cantón Chone - Muñoz Cedeño, Jhaydeé María (2023)
The present research focuses on t analyzing and improving administrative and operational processes and procedures in the Autonomous Decentralized Rural Parish Government of Canuto, aiming to reduce time and enhance value-added for the customer. By applying the AVA methodology (Add, Value, Save) and optimizing inspection processes, the goal is to increase efficiency and agility within the institution. The research methodology used was descriptive, fieldwork-based, and bibliographic. Visits to the GADPR, document review, process and procedure analysis, interviews, and observations were conducted. The obtained results revealed the need to align workflows, simplify procedures, implement technological solutions, and provide training to personnel to strengthen continuous improvement. Redundant and non-essential steps were identified in the inspection processes, which were analyzed and reduced through the AVA methodology. The implementation of proposed improvements will allow for faster and more satisfactory service, freeing up time and resources that can be allocated to priority activities. In conclusion, it is recommended to establish clear response times, provide training to personnel, implement monitoring and evaluation systems, and promote continuous improvement to optimize processes and procedures in the GADPR of Canuto. These actions will strengthen institutional reputation, improve customer satisfaction, and achieve greater service delivery efficiency.